Bivariate low flow return period analysis in the Mahanadi River basin, India using copula. Issue 1 (2nd January 2020) - Sahoo, Bibhuti Bhusan; Jha, Ramakar; Singh, Anshuman; Kumar, Deepak
ABSTRACT: Assessments of low flows of major river of India are essential for effective management of drought and irrigation water demand/supply mechanism. In the present work, bivariate low flow frequency analysis of Mahanadi basin, that had significant variations in hydrological behaviour from upstream to downstream, was done for two major low flow characteristics, namely, severity ( S ) and occurrence ( O ) . Three Copulas have been tested for their applicability to estimate the joint return period of low flow at 2, 5, 10, 20, 50 years return periods. According to the Akaike information criterion (AIC) value, the Clayton Copula and the Frank Copula were found to be the most suitable for the stations in Basantapur and Kantamal, respectively. Further, the conditional low flow return periods were estimated and were found useful for low flow management and ecological analysis in the Mahanadi basin.